Sectoral dimensions of Poland's investment development path revisited. Issue 2 (June 2019) - Gorynia, Marian; Nowak, Jan; Trąpczyński, Piotr; Wolniak, Radosław
Abstract: The purpose of the present paper is to determine the changes of the sector and industry structure of FDI and to confront the observed patterns with the hypotheses or predictions derived from the IDP model. At the heart of the IDP model lies the concept of net outward investment (NOI). The NOI position (NOIP), broken down by the main sectors and component industries of the Polish economy, is analyzed for the period of 1996–2016. We develop a conceptual framework of the sectoral shifts in the composition of NOIP along its different stages. Subsequently, our panel regression analysis indicates that the relative share of a sector in inward and outward FDI stocks is positively related to its level of technological intensity and its level of service intensity.